Folk festivals of the Philippines - Martires, Myrna (Aspects of Philippine culture, 1968)
Cultural performances discussed: District Fiesta of Quiapo - Jan 9, Feast of the Three Kings- Jan 6, Ati-Atihan Festival-Jan 20-21, Holy Week in the Philippines, Carabao Festival- Bulacan- Nueva Ecija, Rizal Provnces May 14, Harvest Festival- Sariaya and Lucban of Quezon Province, Santacruzan- May, Bocaue River Festival in honor of the Holy Cross of Wawa - Bocaue Bulacan July, Pateros Town Fiesta - July 29, Penafrancia Fiesta in Naga City- Camarines Sur September, La Naval de Manila- Quezon City October, Christmas Lantern Festival in San Fernando- Pampanga December 24.